Citizenship: A Very Short Introduction - Bellamy, Richard (New York Oxford University Press, 2008)
Interest in citizenship has never been higher. But what does it mean to be a citizen in a modern, complex community? Richard Bellamy approaches the subject of citizenship from a political perspective and, in clear and accessible language, addresses the complexities behind this highly topical issue.
Includes Index and Illustrations.
Keywords: Citizenship